2018
DOI: 10.3892/ol.2018.9254
|View full text |Cite
|
Sign up to set email alerts
|

D Rhamnose β‑Hederin against human breast cancer by reducing tumor‑derived exosomes

Abstract: D Rhamnose β-hederin (DRβ-H), a novel oleanane-type triterpenoid saponin isolated from the traditional Chinese medicinal plant Clematis ganpiniana, has been demonstrated to be effective against various types of tumor. However, the exact role of DRβ-H on breast cancer remains largely unresolved. In the present study, it was observed that DRβ-H exhibited anti-proliferative and pro-apoptotic activity in human breast cancer cells (MCF-7/S). DRβ-H was able to inhibit exosome secretion, and the level of exosomes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…D Rhamnose β-hederin (DRβ-H), a triterpenoid saponin, could reduce the growth and apoptosis of cancer cells by inhibiting the secretion process of exosomes. Subsequently, some specifically encapsulated miRNAs, including miR-130a and miR-425, were also downregulated [114]. Shikonin (SK) could also suppress exosome release accompanying with reduced miR-128 [115] and restrain the cancer-promoting effects of preadipocytes through disturbing miR-140/SOX9 signaling [116].…”
Section: Therapeutic Methods Targeting At the Exosomal Micrornasmentioning
confidence: 99%
“…D Rhamnose β-hederin (DRβ-H), a triterpenoid saponin, could reduce the growth and apoptosis of cancer cells by inhibiting the secretion process of exosomes. Subsequently, some specifically encapsulated miRNAs, including miR-130a and miR-425, were also downregulated [114]. Shikonin (SK) could also suppress exosome release accompanying with reduced miR-128 [115] and restrain the cancer-promoting effects of preadipocytes through disturbing miR-140/SOX9 signaling [116].…”
Section: Therapeutic Methods Targeting At the Exosomal Micrornasmentioning
confidence: 99%
“…However, it has been recently suggested that miRNA biosynthesis can occur in extracellular vesicles in breast cancer [ 168 ], providing a new level of complexity. In either case, treatment with compounds that stop this process can prevent breast cancer progression by reducing miRNA-derived extracellular vesicles [ 169 , 170 ]. CSCs also secrete miRNAs in extracellular vesicles [ 171 ], suggesting that the successful treatment of breast cancer may lie in the ability to stop the secretion of extracellular vesicles containing miRNAs.…”
Section: Use Of Mirnas As Biomarkers For Breast Cancermentioning
confidence: 99%
“…D Rhamnose β-hederin from the vine Clematis ganpiniana (H.Lév. and Vaniot) Tamura reduced breast cancer tumor cell exosome production, exosomes which either carry genetic cargo coding for Docetaxel chemoresistance ( Chen et al, 2018b ) or simply pro-metastatic miRNAs, like miR-130 and miR-425 ( Chen et al, 2018a ). Finally, in breast cancer cell lines, Timosaponin A-III, extracted from the plant species Anemarrhena asphodeloides Bunge, has been shown to induce the expression of miR-200c and miR-141, both of which may target c-Myc.…”
Section: Terpenoids and Meroterpenoidsmentioning
confidence: 99%